Reputation detection based on incomplete distribution for mobile agent in wireless sensor networks - Yang Yang; Xiaoyu Jin; Su Yao; Xuesong Qiu; Liu Liu (International Journal of Distributed Sensor Networks)
Mobile agent is a kind of program which can transfer via asynchronous mode independently in the sensor network with outstanding prospects in application. However, due to the openness of the sensor network, mobile agents are facing the threat of security, such as being stolen and modified. How to protect sensors from attacks of malicious mobile agents becomes an important issue in the field. Traditional access control strategies such as hybrid encryption mechanism, partial results of the package, and other methods have some defects in the application. We design a multisensor interaction trust model with complete β distribution and introduce incomplete β distribution to optimize the trust model according to the actual situation of detection data loss for mobile agent system in the wireless sensor networks. In addition, the introduction of the malicious behavior feedback mechanism ensures the security of sensors in the mobile agent system. The experimental results show that the reputation model of incomplete β distribution can simulate the actual situation well, resist the attacks of malicious agents, and ensure the security of sensors in the system.